Kyllo v. United States and the Partial Ascendance of Justice Scalia's Fourth Amendment - Richard H. Seamon (Washington University Law Quarterly, 2001)
The recent terrorist attacks on the United States will inspire a call for intrusive, new surveillance technology. When used by the government, this technology strains the Fourth Amendment. That is because the technology often can enable the government to gather information in ways that are hard to analyze under a provision that seems to address physical interferences with tangible things (i.e., “searches” and “seizures” of “persons, houses, papers, and effects”). Illustrating the strain, the government’s use of an electronic listening device prompted the United States Supreme Court to modify the definition of a Fourth Amendment “search” in the landmark case of Katz v. United States. Recently, the Court again confronted the question of whether government surveillance technology constituted a “search” in Kyllo v. United States. The thesis of this Article is that Kyllo reflects a significant, though subtle, departure from Katz, for which Justice Scalia is primarily responsible. This Article examines Kyllo in four steps. Part I briefly describes the facts and procedural history of the case. Part II examines the facets of the majority and dissenting opinions that will receive the most attention from lower courts and practitioners. Part III examines Kyllo beneath the surface to demonstrate its doctrinal importance.
Keywords: Infrared imaging; Right of privacy; Scalia; Antonin; 1936-; Searches and seizures